Sistem penghantaran tesis dalam talian Perpustakaan Sultanah Zanariah - Nasir, Haslina (2002)
The purpose of the thesis is to provide an experience in scholarship which will enduring value to the student in understanding how new technology is acquired and communicated within their chosen field. Thus thesis or dissertation should provide tangible evidence of student's development as a scholar and to discover and effectively communicate research findings. Therefore, ETD is a best solution for organizing the source of information from the research that has been conducted and to make information about theses available quickly and easily and allow the scholar to continue what they have always done and participate in creation of the knowledge. There are four element that have been stressed during the research which include the role of digital library, producing digital thesis, electronic delivery and the library storage from the library site. Besides can ensuring that the security and the accuracy of the record and data of the theses for the faculty. There are 4 modules in Sistem Penghantaran Tesis Dalam Talian Perpustakaan Sultanah Zanariah which consist of Student Module, Faculty Administrator Module, PSZ Administrator Module and Searching Theses Module. Hopefully with the development of the system, it will provides economic and educational advantages not only to the library, but both to student and to the university